2014
DOI: 10.1007/s11999-013-3256-4
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Adjacent Segment 10 Years After Anterior Lumbar Interbody Fusion for Low-Grade Isthmic Spondylolisthesis

Abstract: Background Adjacent segment degeneration is a longterm complication of arthrodesis. However, the incidence of adjacent segment degeneration varies widely depending on the patient's age and underlying disease and the fusion techniques and diagnostic methods used. Questions/purposes We determined (1) the frequency of adjacent segment degeneration and increased lordosis on imaging tests, (2) the frequency and severity of clinical sequelae of these findings, including revision surgery, and (3) the sequence of dege… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 31 publications
2
25
0
1
Order By: Relevance
“…Limited studies, however, have reported on the details of procedures using the APS. As an effective means of pedicle screw xation, APS not only provides superior postoperative spinal stability for ALIF, but allows a shorter operating time, less blood loss, and minimal posterior muscle damage [4,5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Limited studies, however, have reported on the details of procedures using the APS. As an effective means of pedicle screw xation, APS not only provides superior postoperative spinal stability for ALIF, but allows a shorter operating time, less blood loss, and minimal posterior muscle damage [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…However, ALIF-PPS would increase the number of incision, the operating time and blood loss. While stand-alone ALIF has potential bene t of shorter operating time, less blood loss and sparing of posterior muscle damage [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that ALIF with PPF can be performed to attain the surgical goals and successful outcomes in the management of isthmic spondylolisthesis. 2,7 However, hypoplasia of the lumbar pedicle also increases the difficulty of performing PPF. In the cases featured in this paper, we performed PPF only for normal pedicles.…”
Section: Discussionmentioning
confidence: 99%
“…This procedure offers an anterior access at L4-L5 and L5-S1 levels, allowing for a complete discectomy, better end-plate preparation, direct insertion of the cage, and adequate distraction for the development of lordosis. Moreover, this approach does not damage the posterior vertebral elements so that it can result in less postoperative axial back pain and a reduced possibility of adjacent segmental disease (ASD) (20). The complications described in the ALIF include damage to the abdominal viscera and anterior lumbar vessels, retrograde ejaculation, intestinal adhesions, and abdominal hernia (21)(22)(23).…”
Section: Advantages and Disadvantages Of The Lumbar Fusion Techniquesmentioning
confidence: 99%